A drag force correlation for approximately cubic particles constructed from identical spheres. (17th February 2015) - Chen, Y.; Third, J.R.; Müller, C.R.
Abstract: The lattice Boltzmann method has been used to compute the drag force acting on assemblies of approximately cubic particles constructed from eight spheres for a wide range of Reynolds numbers. Based on the simulation data we propose a new drag force correlation for assemblies of approximately cubic particles. We have compared the drag force obtained with that predicted by the correlation proposed byBeetstra et al. (2007), originally proposed for spheres, by considering either the drag acting on individual spheres or the drag acting on an approximately cubic particle composed of eight spheres. The comparisons showed that Beetstra׳s correlation cannot predict the system well. The correlation proposed in this paper enables Euler–Euler and Euler–Lagrangian simulations of approximately cubic particles, allowing the influence of the solid volume fraction in these models to be assessed. Abstract : Graphical abstract: Abstract : Highlights: The LBM has been used to develop a drag force correlation for approximate cubes. Comparison with correlations for spheres indicates that particle shape is important. The new correlation allows an examination of particle shape effects in CFD-DEM models.